Looking at Charles Bonnet Syndrome: Prevalence and Experiences of Patients Attending a Vision Rehabilitation Clinic. (September 2018) - Ord, Lisa M.; Henderson, Amy; Christiansen, Robert M.
Introduction: The objective of this study was to determine the prevalence of Charles Bonnet syndrome in a population of patients seen in a vision rehabilitation clinic and to gain deeper insight into the content of visual hallucinations that are experienced. Methods: This investigation was a retrospective review of medical record vision rehabilitation evaluations from 100 adult patients who were seen consecutively in a vision rehabilitation clinic. Data collected included age, gender, eye condition, current medications, other medical diagnoses, current living situation, and responses to questions about Charles Bonnet syndrome symptomatology. Results: Eight participants were excluded from analysis due to diagnosis of cognitive impairment or a current anticholinergic medication. A total of 25.0% (n = 23) of eligible patients with visual impairments reported visual hallucinations that met the definition of Charles Bonnet syndrome. Images of people (35%) were the most common hallucinations reported by participants, followed by images of animals (26%). Discussion: The occurrence of this syndrome in our study is near the mid-range of estimated prevalence in the professional literature. Implications for practitioners: Individuals with this syndrome are hesitant to disclose that they are experiencing hallucinations for fear of being seen as having dementia or psychosis. An important concept for vision professionals, especially those offering visual rehabilitation, is integrating screening for Charles Bonnet syndrome into their care planning. Demonstrating that the syndrome is not a rare occurrence helps raise awareness of it in people with vision loss, thus explaining it as not so unusual and facilitating a discussion between patients and professionals that will reduce the apprehension that many individuals with visual impairments have that these hallucinations are a sign of more concerning conditions.